Los estilos de aprendizaje, según los modelos de Kolb, Felder y Silverman: ventajas y desventajas - Carlos Alberto Vásquez Villanueva; Nicole Sol Briceño Ledesma; Shaira Garamendi Revatta; Eyner Quintana Vargas (My University, 2022)
This article has been designed with the aim of determining the most significant advantages of learning styles, according to the models of Kolb, Felder and Silverman, for the development of teaching-learning of students at the primary level. It is important to manage suitable didactic strategies for the development of learning styles. The review shows the conceptualization and analysis of the Kolb model and the Felder and Silverman model. This study is completely qualitative, and was carried out by reviewing various scientific articles, theses, and journals from different search engines: Redalyc, Scielo, Google Scholar, and others. In short, it can be concluded that the Felder and Silverman learning model contributes significantly to student learning, as well as helping teachers to develop cognitive and intuitive skills.
Keywords: Humanities; Cartography; Psychology; Art; Geography; Humanities; Cartography; Psychology; Art; Geography; Physical Sciences Computer Science Information Systems Educational Innovations and Technology; Social Sciences Social Sciences Sociology and Political Science Diverse Applied Research Studies; Social Sciences Social Sciences Education Educational Outcomes and Influences